2007
DOI: 10.1590/s0102-33062007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Crecimiento secundario inusual en raíz principal de Pfaffia gnaphalioides (L. Fil.) Mart. (Amaranthaceae)

Abstract: RESUMEN -(Crecimiento secundario inusual en raíz principal de Pfaffia gnaphalioides (L. Fil.) Mart. (Amaranthaceae)). Raíces de Pfaffia se comercializan como "ginseng brasilero" y extractos crudos de raíces de Pfaffia glomerata tienen actividad analgésica y desinflamatoria. Pfaffia gnaphalioides es herbácea perenne y crece en el área serrana del sur de la Provincia de Córdoba, Argentina. El objetivo de este trabajo es estudiar el crecimiento secundario inusual en raíz principal de Pfaffia gnaphalioides. Se est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The secondary structures of roots and stems observed in G. marginata show an unusual or anomalous thickening of the vascular cylinder due to the high activity of supernumerary cambia, resulting specially in the formation of abundant reserve tissues. This anomalous thickening is a common phenomenon in the Amaranthaceae (Metcalfe and Chalk, 1950; Menezes et al, 1969; Grosso, 2007; El-Ghamery et al, 2015; Sá et al, 2016) and Chenopodiaceae (Metcalfe and Chalk, 1950; Krumbiegel, 1998). In G. albiflora , root secondary growth was also considered atypical (Jáuregui et al, 2014) as the authors showed that the successive rings are formed from a lateral meristem producing parenchyma outward, supernumerary cambia and parenchyma inward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The secondary structures of roots and stems observed in G. marginata show an unusual or anomalous thickening of the vascular cylinder due to the high activity of supernumerary cambia, resulting specially in the formation of abundant reserve tissues. This anomalous thickening is a common phenomenon in the Amaranthaceae (Metcalfe and Chalk, 1950; Menezes et al, 1969; Grosso, 2007; El-Ghamery et al, 2015; Sá et al, 2016) and Chenopodiaceae (Metcalfe and Chalk, 1950; Krumbiegel, 1998). In G. albiflora , root secondary growth was also considered atypical (Jáuregui et al, 2014) as the authors showed that the successive rings are formed from a lateral meristem producing parenchyma outward, supernumerary cambia and parenchyma inward.…”
Section: Discussionmentioning
confidence: 99%
“…The underground reserve system of G. marginata is mainly a tuberous root, capable of resprouting due to the presence of buds, also described in Pfaffia gnaphalioides (Grosso, 2007) and in tuberous roots of Vernonia brevifolia (currently Lessingianthus brevifolius ) (Hayashi and Appezzato-da-Glória, 2007) and V. oxylepis (Vilhalva and Appezzato-da-Glória, 2006), both inulin accumulating Asteraceae species. The presence of buds in belowground organs allows the regeneration of the aerial parts after drought, fire or any other environmental disturbance (Klimesová and Klimes, 2007), while the reserve compounds therein supplies energy and carbon to guarantee resprouting, growth, and ultimately, species survival.…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de comuns em caules de diversas espécies de lianas, principalmente por sua conexão com o hábito, as variações cambiais ocorrem também nas raízes, de forma semelhante aos caules, em vários grupos de plantas, como Amaranthaceae, Basellaceae, Nyctaginaceae, Passifloraceae, Phytolaccaceae, Polygonaceae e Sapindaceae (Grosso 2007;Rajput et al, 2010;El-Ghamery et al 2015;Carlquist 1999;Carlquist 2004;Hearn 2009;Mikesell 1979;Horak 1981;Rajput 2015). Os trabalhos de Gabrielli (1992), Martinelli et al (2008) e Singh & Misra (2012) demonstram que também as raízes de espécies de Bignonieae desenvolvem cunhas de floema semelhantes às encontradas em caules, entretanto esses estudos se mostram rasos ou incompletos quanto a maiores aspectos anatômicos e estruturais.…”
Section: Bignoniaceae E Bignonieaeunclassified